2020
DOI: 10.17014/ijog.8.1.1-9
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake Potential Hazard Analysis of Palembang City, Sumatra Island

Abstract: Most of the destructive earthquakes in Sumatra are dominated by thrust mechanisms that occur due to the process of subduction and some earthquakes with strike-slip fault sources such as the Sumatra fault and northwestern Sumatra. Subduction zones along western Sumatra and Sumatran fault zones are active seismic sources of earthquake events. The seismotectonics of South Sumatra can be affected by earthquakes triggered by these seismic sources. In this study, an estimation and analysis of the potential for earth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…This study's motivation was to perform a probabilistic seismic hazard analysis using the source area's surface displacement data off the west coast of northern Sumatra on March 28, 2005. Based on the previous study by Triyoso et al (2021), the Sumatran Fault's impact on the seismic hazard analysis in the vicinity of the major subduction event could be neglected. Considering the availability of the recorded pre-and co-seismic GPS data in the (Frankel, 1995) weighted by normalizing the estimated seismic moment rate model (C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study's motivation was to perform a probabilistic seismic hazard analysis using the source area's surface displacement data off the west coast of northern Sumatra on March 28, 2005. Based on the previous study by Triyoso et al (2021), the Sumatran Fault's impact on the seismic hazard analysis in the vicinity of the major subduction event could be neglected. Considering the availability of the recorded pre-and co-seismic GPS data in the (Frankel, 1995) weighted by normalizing the estimated seismic moment rate model (C).…”
Section: Resultsmentioning
confidence: 99%
“…The study area is around the subduction zone of M w 8.6. Based on the previous results (Triyoso et al, 2021), the Sumatran Fault's impact could be neglected.…”
Section: Introductionmentioning
confidence: 99%
“…This is evidenced by the large number of earthquake damage data in several regions in Indonesia. Most of the destructive earthquakes in Sumatra are dominated by earthquakes with thrust mechanisms that occur due to the subduc-tion process and strike-slip mechanisms, such as the Sumatra Subduction Zone (SSZ) and Sumatra Fault Zone (SFZ) (Triyoso et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Still in disaster mitigation efforts for Bengkulu Dewi Susiloningtyas [8] made a spatial pattern of earthquake-prone areas by calculating the PGA value in 2010 -2018 and determining the tsunami inundation area based on wave heights of 5 m, 20 m, and 25 m. It was found that the high risk area is on the southern coast of Bengkulu in the Kampung Melayu sub-district with an estimated affected area of 653.69 Ha. The results of research by Wahyu Triyoso and Aris Suwondo [9] who evaluated PGA by including an amplification factor calculated using the Horizontal-Vertical Spectral Ratio (HVSR) method with a subduction earthquake source, which is greater than the estimated ground shaking due to a shear fault source and a medium to deep earthquake source. for the city of Palembang, gives the result that the city of Palembang has a potential shock of about 35 gal, which is probably caused by the source of the megathrust earthquake.…”
Section: Introductionmentioning
confidence: 99%